INSTALASI KELISTRIKAN MESIN PENCETAK ARANG BRIKET BATOK KELAPA SKALA USAHA MIKRO KECIL dan MENENGAH (UMKM) - Hidayat, Taufik; Apnena, Riri Damayanti (Jurnal Mahasiswa Terapan, 2024)
A charcoal briquette printing machine is a device specifically designed to produce briquette charcoal in bulk. Charcoal briquettes are solid charcoal powder made from other biomass waste. Biomass waste management: Many industrial and agricultural processes produce biomass waste such as coconut shell charcoal powder, wood charcoal powder, straw powder, rice husk charcoal powder or other agricultural waste. The planning method used in making the electrical system for the micro smalll and medium enterprisess scale coconut shell charcoal briquette printing machine includes preparation of tools and materials, planning and design, assembly process, finishing process, and performance testing of the micro small and medium enterprisess scale coconut briquette charcoal printing machine. The average results from testing this charcoal briquette printing machine is that it is capable of making 1 kg of briquetted charcoal in 1.31 minutes and produces 15 briquettes of charcoal with an average weight of 65 grams. In 1 hour this machine is able to print 675 briquettes of charcoal in 45 kg of powdered wood charcoal. for 1 day this machine can operate for 8 working hours and can produce 360 kg of charcoal powder and produce 5,400 charcoal briquettes.